The Good Research Guide: Research Methods for Small-Scale Social Research Projects - Martyn Denscombe (New York Open University Press, 2021)
The Good Research Guide provides practical and straightforward guidance for those who need to conduct small-scale research projects as part of their undergraduate, postgraduate or professional studies. The 7th edition covers topics in a clear, user-friendly style outlining the key points and explaining why they are important. The new edition has been updated throughout and has additional material on topics such as social media research, online surveys, image-based research and participatory action research. It also features new chapters on how to prepare for a research project, with specific guidance on: - how to undertake a literature review - how to write a research proposal - how to ensure the research is ethical - how to locate the project within a research paradigm Full of practical advice and valuable examples, this is the go-to book for students looking to improve their research skills.
Keywords: Research; Nonfiction; Research Methods (BIN2044-N)